Três ensaios em demografia de empresas - Céspedes, Carlos Hernán Rodas (2017)
(Ensaio I) This study investigates the demographics of companies at Rio Grande do Sul State from 2006 to 2013. First, the birth, mortality and turnover of companies are quantified, as well as their survival over time. Then, these demographic events are analyzed by size, economic activity, and geographic location. For this purpose, an identified database is used, which allows the longitudinal monitoring of all formal companies existing in Rio Grande do Sul over the period under study. (Ensaio II) This paper proposes an empirical research on the survival of the companies of Rio Grande do Sul State for the period 2007-2013. The Kaplan-Meier procedure is applied to obtain the functions of survival of the companies, according to the geographic location, the economic activity and the size. Then, the Cox procedure is applied, in order to determine the effect of the size of the companies on the survival time. The results obtained show that survival is relatively higher: in the companies with the largest number of employed persons; in the manufacturing industry and financial activities; and located in the Northeast region of Rio Grande do Sul state. (Ensaio III) The objective of this paper is to analyze the birth of companies in the counties of Rio Grande do Sul State between 2007 and 2013. For this, exploratory analysis of spatial data and the panel data regression are used. The results indicated the existence of spatial autocorrelation of the birth of companies and the formation of some clusters of the counties with high births of companies. The spatial auto regression (SAR) model evidenced the spillover effect of the birth of companies and made it possible to measure the direct and indirect impacts of the independent variables on the birth of companies.